ANALYSIS OF THE EFFECT OF PLYOMETRIC TRAINING ON INCREASING JUMPING ABILITY IN VOLLEYBALL - Ikadarny; Suriah Hanafi (International Journal of Teaching and Learning, 2025)
Increasing jumping ability is one of the key factors in achieving achievements in volleyball. Plyometric training, known to be effective in improving jumping ability and muscle strength, has been the focus of this study to evaluate its effects on volleyball athletes. Through comprehensive literature analysis, this research aims to collect and synthesize data from various existing studies regarding the application of plyometric training in volleyball training, to understand the concrete benefits of this training method on improving athletes' jumping abilities. A literature search was carried out on various databases and scientific journals that publish research related to sport, fitness and exercise physiology, with certain inclusion criteria to ensure the relevance and quality of the data. The results of the analysis show that plyometric training significantly contributes to improving the jumping performance of volleyball athletes. This is reflected in increased vertical jump performance, reaction time, and muscle contraction speed which are vital in volleyball games. The implementation of plyometric training that is structured and adaptive to the needs of individual athletes shows more optimal results, indicating that personalization of training plays an important role. Additionally, the integration of plyometric exercises with the overall training program, including aspects of strength, speed, and endurance, was identified as an effective strategy for achieving maximum results. Based on these findings, it is concluded that plyometric training is an important component in volleyball training to improve athletes' jumping ability. This research recommends the use of plyometric training as part of a volleyball athlete's preparation, while paying attention to individual needs and preventing the risk of injury to maximize the benefits of training.